2020
DOI: 10.1111/tmi.13389
|View full text |Cite
|
Sign up to set email alerts
|

High fever after sublingual administration of misoprostol for treatment of post‐partum haemorrhage: a hospital‐based, prospective observational study in Argentina

Abstract: objective To characterise the occurrence of fever (≥38.0°C) after treatment for post-partum haemorrhage (PPH) with sublingual misoprostol 800 mcg in Latin America, where elevated rates of misoprostol's thermoregulatory effects and recipients' increased susceptibility to high fever have been documented.methods A prospective observational study in hospitals in Argentina enrolled consenting women with atonic PPH after vaginal delivery, eligible to receive misoprostol. Corporal temperature was assessed at 30, 60, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…A large multicenter study [44] reported an unusually high rate of fever >40°C (36%) in Ecuadorian women who received 800 μg of misoprostol sublingually compared with other participants (0-9%) who received the same regimen. Since the incidence of fever varies greatly in different populations, there is hypothesis that genetic factors may play a role in misoprostol-induced fever [45]. Some studies [46] suggest that genetic variability in ABCC4 and the resultant higher level of misoprostol acid in the brain lead to hyperpyrexia in pregnant women.…”
Section: Cnsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large multicenter study [44] reported an unusually high rate of fever >40°C (36%) in Ecuadorian women who received 800 μg of misoprostol sublingually compared with other participants (0-9%) who received the same regimen. Since the incidence of fever varies greatly in different populations, there is hypothesis that genetic factors may play a role in misoprostol-induced fever [45]. Some studies [46] suggest that genetic variability in ABCC4 and the resultant higher level of misoprostol acid in the brain lead to hyperpyrexia in pregnant women.…”
Section: Cnsmentioning
confidence: 99%
“…However, this is not the only influence on postnatal fever. There appear also to be other effects that could be genetic or cultural [44,45]. Clinically, it is worth noting that fever as the side effect of misoprostol and fever caused by postpartum infection need to be distinguished more carefully [83].…”
Section: Misoprostolmentioning
confidence: 99%
“…Women who were in active labor and did not have an allergy to a prostaglandin or had a planned caesarean section were able to participate in the study. Four 200 μg of misoprostol were placed under the tongue if their hemorrhage bleeding reached 500 mL ( Durocher et al, 2020 ) [A]. Participants' temperature was checked in 30-min intervals.…”
Section: Prostaglandins and Analogues [Seda-35; Seda-36 604; Seda-37 494; Seda-38 428; Seda-42]mentioning
confidence: 99%
“…This perception can affect prescription behaviour, potentially leading to repeated administration, changing to other less effective uterotonics and the use of combinations of different types of uterotonics 27. This behaviour can expose women to excessive doses of oxytocin and misoprostol, and associated adverse events including maternal and perinatal death 14 16 28–30. In theory, women exposed to repeated doses of degradation products from deteriorated drugs could also develop toxicity-related adverse effects.…”
Section: Introductionmentioning
confidence: 99%